Dancing in Shadows: Sihanouk, the Khmer Rouge, and the United Nations in Cambodia - Widyono, Benny (Rowman & Littlefield Publishers, 2007)
This fascinating book recounts the remarkable tale of a career UN official from Indonesia caught in the turmoil of international and domestic politics swirling around Cambodia during the tumultuous period after the fall of the Khmer Rouge. Writing from his experience first as a member of the UN transitional authority and then as a personal envoy to the UN secretary-general, Benny Widyono re-creates the fierce battles for power centering on King Norodom Sihanouk, the Khmer Rouge, and Prime Minister Hun Sen. A simultaneous insider and outsider, he also untangles the competing and conflicting agendas of the key international players, especially the United States, China, and Vietnam. He argues that great-power geopolitics throughout the Cold War and post–Cold War eras triggered and sustained a tragedy of enormous proportions in Cambodia for decades, ultimately leading to a flawed peace process. Widyono tells the inside story of the massive UN operation in Cambodia, the largest and most challenging in the organization's history to that time and long considered a model for UN operations elsewhere. He draws not only on his vantage point as part of the UN bureaucracy, but also as a local UN official in the rural Cambodian province of Siem Reap, the site of Angkor Wat. As a fellow Southeast Asian with no geopolitical axe to grind, Widyono was able to win the respect of Cambodians, including the once and future king, Norodom Sihanouk, whose decline after fifty years as his country's leading figure is vividly portrayed. Putting a human face on international operations, this book will be invaluable reading for anyone interested in Southeast Asia, the role of international peacekeeping, and the international response to genocide.